DAILY AS A SOURCE OF INFORMATION FOR THE CHOICE OF RESEARCH ISSUES IN HEALTH SCIENCES (Part IV) - Balarezo-López, Gunther (2021)
Most people do not have access to the information, and if it is about science subjects, the misinformation is even greater. The scientific press is precisely the specialty that is in charge of being the link between scientific advances and society, so that the news is disseminated and made understandable to the population. In this sense, a review was made of articles published in the Diario El Comercio of Lima, Peru, which were related to health. It was found that newspapers publish very little science and technology related news for different reasons. In this sense, a complementary work between scientists and journalists is recommended so that the news related to science is as truthful and understandable as possible for people who are not specialists in the subject. Keywords: diary – healthcare professionals – health sciences – science journalism – topic choice